Theatre and Critical Consciousness in Teacher Education (LEARNing Landscapes, 2008)
Education for social justice, or critical pedagogy, is designed to empower learners and often uses the arts as primary pedagogical means. It has gained increasing attention in teacher education in recent years. However, the author’s use of critical approaches to theatre with teacher education students raised serious questions about their limited level of consciousness, or empowerment, but also alternate possibilities, including theatre, for empowering students during their teacher education programs.
Keywords: education; social justice; critical pedagogy; learner; arts; teacher education; theatre; empowering; consciousness